A Critical Review of Intrusion Detection Systems and Its Applicability in Mobile Ad Hoc Networks - Chaudhary, A; Shrimal, G (International Journal of Computer Sciences and Engineering, 2025)
Mobile Ad hoc networks (MANETs) provide autonomous communication between the mobile nodes in the absence of predefined infrastructure. This property of MANETs makes it more vulnerable from conventional networks. Due to this reason, prevention mechanism such as authentication and cryptography techniques alone are not capable to protect it so that intrusion detection system (IDS) employed to facilitate the identification of intrusions in MANETs. This paper examined the detailed analysis on each class of intrusion detection systems that have been proposed in MANETs for preventing the network layer attacks and also focuses the further research areas in MANETs